Pengaruh EPS, ROE, dan DER terhadap Nilai Perusahaan pada Emiten LQ45 BEI 2020–2024 - Nabilah Safitri; M. Mustaqim; Achmad Zaki; Devika Cherly Putrihadiningrum (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
Firm value is an important indicator that reflects investors' perceptions of a company's performance and future prospects. However, previous studies examining the influence of fundamental corporate factors on firm value have produced inconsistent findings. This study aims to analyze the effect of Earnings Per Share (EPS), Return on Equity (ROE), and Debt to Equity Ratio (DER) on firm value, proxied by Price to Book Value (PBV), in companies listed in the LQ45 Index of the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data analyzed through panel data regression. Model selection was conducted using the Chow Test, Hausman Test, and Lagrange Multiplier Test, which identified the Random Effect Model (REM) as the most appropriate model. The results indicate that, partially, EPS has a negative and significant effect on firm value, ROE has a positive and significant effect on firm value, while DER has a positive but insignificant effect on firm value. Simultaneously, EPS, ROE, and DER have a significant effect on firm value. The coefficient of determination (R²) of 14,13% indicates that variations in firm value can be explained by these three variables, while the remaining 85,87% is influenced by other factors outside the research model. This study provides empirical evidence that profitability, as measured by ROE, is the most influential factor in enhancing firm value. Furthermore, investors’ assessments of firms are influenced not only by financial indicators but also by external factors and future business prospects.